2008
DOI: 10.1021/ol801512q
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Direct Copper-Catalyzed Alkenylation of Oxazoles with Bromoalkenes

Abstract: A copper-catalyzed direct alkenylation of oxazoles with bromoalkenes has been developed. The method is both regio- and stereoselective and tolerates a variety of functional groups. A wide range of 2-E-vinyl-substituted oxazoles were obtained in high yields including the highly fluorescent alkaloid annuloline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(58 citation statements)
references
References 43 publications
2
55
0
1
Order By: Relevance
“…[193] Highly regio-and diastereoselective copper-catalyzed direct alkenylations of oxazoles were realized with vicinal diamine 272 as the ligand. [194] As was previously observed, the addition of the strong base LiOtBu was mandatory. The scope of this procedure was highlighted by the efficient synthesis of alkaloid annuloline ((E)-271; Scheme 101).…”
Section: Copper-catalyzed Direct Arylationmentioning
confidence: 71%
“…[193] Highly regio-and diastereoselective copper-catalyzed direct alkenylations of oxazoles were realized with vicinal diamine 272 as the ligand. [194] As was previously observed, the addition of the strong base LiOtBu was mandatory. The scope of this procedure was highlighted by the efficient synthesis of alkaloid annuloline ((E)-271; Scheme 101).…”
Section: Copper-catalyzed Direct Arylationmentioning
confidence: 71%
“…[193] Durch Verwendung des vicinalen Diamins 272 konnten hoch regio-und diastereoselektive kupferkatalysierte direkte Alkenylierungen von Oxazolen realisiert werden. [194] Auch hier war die Zugabe der starken Base LiOtBu obligatorisch. Die Anwendungsbreite dieses Verfahrens wurde anhand einer effizienten Synthese des Alkaloids Annulolin (E-271) demonstriert (Schema 101).…”
Section: Arylchlorideunclassified
“…In these instances, a very few number of heterocycles were studied. Grierson et al [2] reported direct alkenylation of 5-phenyloxazoles with (E)-β-bromostyrenes under copper catalysis. Other groups have extended this methodology to the palladiumcatalyzed alkenylation of other oxazoles, including 5-aryloxazoles [3] and ethyl oxazole-4-carboxylate.…”
Section: Introductionmentioning
confidence: 99%